2016
DOI: 10.4254/wjh.v8.i31.1327
|View full text |Cite
|
Sign up to set email alerts
|

Liver resection for early hepatocellular cancer: Comparison of centers in 3 different countries

Abstract: AIMTo compare patients who underwent resection of early stage hepatocellular cancer (HCC) in three different countries.METHODSThis retrospective study characterizes 573 stage I/II HCC patients treated with liver resection in 3 tertiary-referral centers: Tokyo (n = 250), Honolulu (n = 146) and Shanghai (n = 177).RESULTSShanghai patients were younger, predominantly male, hepatitis-B seropositive (94%) and cirrhotic (93%). Tokyo patients were older and more likely to have hepatitis-C (67%), smaller tumors, low al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Reflecting its predominantly Asian and Pacific Islander demographic, Hawaii has one of the highest incidence rates of liver cancer in the US, with an age-adjusted incidence rate of 11.0 per 100,000 that is considerably higher than the overall US rate of 7.6 per 100,000 [ 4 ] . Given that the distribution of HCC risk factors in Hawaii differs from that of both Asia and the continental US [ 5 7 ] , studies involving cohorts from Hawaii may provide additional insights into the disease.…”
Section: Introductionmentioning
confidence: 99%
“…Reflecting its predominantly Asian and Pacific Islander demographic, Hawaii has one of the highest incidence rates of liver cancer in the US, with an age-adjusted incidence rate of 11.0 per 100,000 that is considerably higher than the overall US rate of 7.6 per 100,000 [ 4 ] . Given that the distribution of HCC risk factors in Hawaii differs from that of both Asia and the continental US [ 5 7 ] , studies involving cohorts from Hawaii may provide additional insights into the disease.…”
Section: Introductionmentioning
confidence: 99%
“…Wong LL [17] reported that elevated alpha-fetoprotein levels, low levels of albumin and tumours > 5 cm in size were associated with increased 1-year mortality after hepatic resection for early-stage hepatocellular cancer in a retrospective study. Kondo K [18] reported that alkaline phosphatase (ALP, > 125 U/L), alpha-fetoprotein (AFP, within 20-400 or > 400 ng/mL), protein induced by vitamin K absence-II (PVIKA-II, within 40-400 or > 400 mAU/mL), tumour number, diameter, pseudocapsule, tumour growth pattern and intratumour haemorrhage were independent prognostic factors for hepatocellular carcinoma patients.…”
Section: Clinical Characteristics Associated With Elderly Hcc Patient...mentioning
confidence: 99%